Antimicrobial Susceptibility of Streptococcus pneumoniae from North America, Europe, Latin America, and the Asia-Pacific Region: Results From 20 Years of the SENTRY Antimicrobial Surveillance Program (1997–2016). (15th March 2019) - Sader, Helio S; Mendes, Rodrigo E; Le, Jennifer; Denys, Gerald; Flamm, Robert K; Jones, Ronald N
Abstract: Background: The SENTRY Antimicrobial Surveillance Program monitors the frequency of occurrence and antimicrobial susceptibility of organisms from various infection types worldwide. In this investigation, we evaluated the antimicrobial susceptibility of Streptococcus pneumoniae isolates collected worldwide over 20 years (1997–2016). Methods: A total of 65 993 isolates were consecutively collected (1 per infection episode) from North America (NA; n = 34 626; 2 nations), Europe (EUR; n = 19 123; 23 nations), the Asia-Pacific region (APAC; n = 7111; 10 nations), and Latin America (LATAM; n = 5133; 7 nations) and tested for susceptibility using reference broth microdilution methods. Resistant subgroups included multidrug-resistant (MDR; nonsusceptible to ≥3 classes of agents) and extensively drug-resistant (XDR; nonsusceptible to ≥5 classes). Results: The isolates were collected primarily from respiratory tract infections (77.3%), and 25.4% were from pediatric patients. Penicillin susceptibility (≤0.06 mg/L) rates varied from 70.7% in EUR to 52.4% in APAC for all years combined. In NA, there was a slight improvement in susceptibility for the first few years of the program, from 66.5% in 1997–1998 to 69.4% in 1999–2000, followed by a decline until 2011–2012 (57.0%). Similar declines in penicillin susceptibility rates were observed in all regions, with the lowest rates of 67.3% in EUR (2011–2012), 41.6% in the APAC region (2007–2008), and 48.2% in LATAM (2013–2014). These declines were followed by improved susceptibility rates in all regions in later program years, with susceptibility rates of 55.6% to 71.8% in 2015–2016 (65.8% overall). Susceptibility rates to ceftriaxone, erythromycin, clindamycin, tetracycline, and trimethoprim-sulfamethoxazole followed a similar pattern, with a decrease in the first 12–14 years and a continued increase in the last 6–8 years of the program. MDR and XDR frequencies were highest in APAC (49.8% and 17.3% overall, respectively) and lowest in LATAM (10.8% and 1.9% overall, respectively). The most active agents for MDR/XDR isolates were ceftaroline (99.7%/99.1% susceptible), tigecycline (96.8%/95.9% susceptible), linezolid (100.0%/100.0% susceptible), and vancomycin (100.0%/100.0% susceptible). Conclusions: S. pneumoniae susceptibility to many antibiotics increased in all regions in the last few years, and these increases may be related to PCV13 immunization, which was introduced in 2010.